Association between falls and depressive symptoms or visual impairment among Japanese young‐old adults. Issue 3 (23rd April 2015) - Kojima, Reiji; Ukawa, Shigekazu; Ando, Masahiko; Kawamura, Takashi; Wakai, Kenji; Tsushita, Kazuyo; Tamakoshi, Akiko
Abstract : Aim: To investigate the association between falls and self‐reported depressive symptoms or visual impairment among young‐old adults. Methods: A total of 1904 participants (986 men and 918 women) aged 64 years from the New Integrated Suburban Seniority Investigation Project from 1996 to 2005, an age‐specific cohort study in Nisshin, Japan, took part in the present study. Depressive symptoms were evaluated using the Geriatric Depression Scale. Visual impairment was assessed using a self‐administered questionnaire. The outcome variable was self‐reported injurious falls at the age of 70 years. Multivariate odds ratios (OR) and 95% confidence intervals (CI) of depressive symptoms and visual impairment for the incidence of falls were calculated using logistic regression models and adjusted for possible confounding factors. Results: Overall, 77 (7.8%) men and 126 (13.7%) women reported falls within the past 1 year at age 70 years. Among women, depressive symptoms and visual impairment were significantly associated with falls after adjusting for potential confounders (OR 1.70, 95% CI 1.09–2.62; OR 2.34, 95% CI 1.45–3.71, respectively), but not among men. Women with both conditions had a significantly increased risk of falls after adjusting for potential confounders (OR 3.50, 95% CI 1.65–7.13) compared with those with neither condition; the association was not significant among men. Conclusions: Depressive symptoms and visual impairment at age 64 years were significantly associated with an increased risk of falls at age 70 years in Japanese women but not in men. The combination of the two symptoms had an even greater association with fall risk.Geriatr Gerontol Int 2015; ●●: ●●–●●.